Assessment of stress, anxiety, and depression among the nursing personnel employed in tertiary care hospital during COVID-19 pandemic - Sain, Sonali; Dey, Indira; Ghosh, Sayanti (Asian Journal of Medical Sciences, 2023)
Background: Work related stress is an important occupational hazard among the forefront healthcare workers like nursing personnel. It is their demanding nature of occupation which exposes them to a higher risk of developing negative mental states. Aims and Objectives: Objectives of the study were to assess the stress, anxiety, and depression among the nursing personnel and their potential risk factors for stress, anxiety, and depression. Materials and Methods: A descriptive observational study was conducted among the nursing personnel employed in a tertiary care hospital in Kolkata. The data collection was done with the help of a predesigned pretested semi-structured questionnaire having information regarding socio demographic profile, history and personal history, and the questions from depression, anxiety and stress scale following permission from Institutional Ethics committee. The data were compiled, analyzed, and presented. Results: The present study found that 29.09%, 40% and 33.64% of the study subjects were suffering from depression, anxiety, and stress, respectively. Nuclear families, staying at hostel, nonspecific symptoms, COVID-19 exposure, and nonspecific symptoms were significant contributing factors for depression. COVID-19 exposure was significantly associated with anxiety. Nuclear families, presence of nonspecific symptoms were significant contributing factor for stress. No significant association was found with age, educational level, marital status, leisure activity, chronic morbidity, testing, and quarantine. Conclusion: Early assessment of the occupational stress, anxiety, and depression among the nursing personnel can initiate targeted intervention strategies. This would improve their personal and professional quality of life which affects the quality of health-care service.